Proton Pump Inhibitor Use and Incident Hypertension in Menopausal Women - Ahmed I. Soliman; Jean Wactawski‐Wende; Amy E. Millen; Shelly L. Gray; Charles B. Eaton; Kathleen M. Hovey; Macarius Donneyong; Nazmus Saquib; Charles P. Mouton; Deepika Laddu; Simin Liu; Daichi Shimbo; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Proton pump inhibitors (PPIs) could affect blood pressure regulation by suppressing gastric acid required for the conversion of oral nitrite into nitric oxide. Whether PPI use is associated with incident hypertension remains unknown. Methods We included 64 720 menopausal women who were free from cardiovascular disease and hypertension at enrollment in the Women's Health Initiative Observational Study (1993–1998). Baseline PPI use and duration were determined using medication inventories. The outcome was physician diagnosed/treated incident hypertension, assessed by self‐report on annual questionnaires. Hazard ratios (HRs) and 95% CIs were estimated using multivariable Cox proportional hazard models for incident hypertension according to baseline PPI use (no/yes) and duration (<1 year, 1–3 years, >3 years). The association between PPI use and 3‐year changes in measured blood pressure was examined using linear regression. Results There were 28 951 cases of incident hypertension after a mean follow‐up of 8.7 years. PPI use was associated with 17% higher risk of hypertension compared with nonuse in the fully adjusted model (HR, 1.17 [95% CI, 1.08–1.27]). Longer PPI use durations were significantly associated with incrementally higher risk of hypertension (HR, 1.13, 1.17, 1.28, respectively; trend P<0.001). The 3‐year change in multivariable‐adjusted mean systolic blood pressure increased significantly for PPI new users (+3.39 mm Hg, P=0.049) compared with never users. Conclusions PPI use was associated with higher risk of diagnosed hypertension in menopausal women, and the risk showed a significant trend according to longer duration of use. Further studies are needed to confirm these findings.